THE EFFECTS OF SOCIAL MEDIA MARKETING ON SPORTS BY USING SPORTS VIDEOS ON FACEBOOK AND INSTAGRAM TO ATTRACT THE PEOPLES TO WATCH MORE SPORTS - Yousaf, Manzar Shabab; Naz, Tabssum; Asghar, Dr. Ejaz; Touqeer, Mohammad; Shahzad, Naeem; Liaquat, Arslan (The journal of contemporary issues in business and government, 2021)
Background: Social media is most commonly used tool to share information these days. So, it is an effective way to approach the target population using social media hence it is becoming popular for promoting social media marketing. Visual content like videos is an effective way for delivering messages. So the researchers are aimed at finding the efficiency of the using visual content (videos) for social media marketing. Methods: Standard questionnaire was designed, and a cross-sectional survey was conducted. 700 individuals were enrolled 456 males and 244 females. Data regarding study was obtained and then analyzed using SPSS. Results: Current studies showed that most of the sample population prefer to watch a video. They provide the reasons such as it provides a clear message and removes confusions. It is time saving and fascinating for the viewers. Instagram and Facebook are more frequently used than any other medium. Conclusion:From this study we may conclude that using videos for social media (Facebook and Instagram) marketing can attract people to watch more sports. One reason is that the Facebook and Instagram are easy to assess and very common in use these days. Moreover, video is easier to deliver the concepts clearly removing the confusions, and the main reason is that it saves the time of people and can effectively deliver the message than any other tool.